2016
DOI: 10.1159/000445284
|View full text |Cite
|
Sign up to set email alerts
|

Infants Operated on for Necrotizing Enterocolitis: Towards Evidence-Based Pain Guidelines

Abstract: Background: Necrotizing enterocolitis (NEC) is known as an extremely painful childhood condition. Objectives: The objective of this study was to explore pain management around NEC-related surgery in our neonatal intensive care unit (NICU) from a chart review of prospectively collected data on 60 operated NEC patients admitted between 2008 and 2013 with a median (IQR) gestational age of 28.3 (25.5-31.6) weeks. Methods: Pain medication data and pain scores (i.e. COMFORTneo and Numerical Rating Scale pain and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The systemic and local inflammation, bowel extension, and ischemic and necrotic processes suggest severe and prolonged visceral pain may be present in infants with NEC [50]. In addition, NEC is associated with an increase in painful interventions, up to 19 times a day, during 5 consecutive days [51].…”
Section: Neurodevelopment In Survivors Of Necmentioning
confidence: 99%
See 1 more Smart Citation
“…The systemic and local inflammation, bowel extension, and ischemic and necrotic processes suggest severe and prolonged visceral pain may be present in infants with NEC [50]. In addition, NEC is associated with an increase in painful interventions, up to 19 times a day, during 5 consecutive days [51].…”
Section: Neurodevelopment In Survivors Of Necmentioning
confidence: 99%
“…In addition, NEC is associated with an increase in painful interventions, up to 19 times a day, during 5 consecutive days [51]. Continuous morphine has been shown to adequately treat the pain associated with NEC in infants who require surgery [50]. However, a single-center study showed that pain assessment was performed in only 30–60% of NEC cases, while analgesia was used in only 52–76% of cases [51].…”
Section: Neurodevelopment In Survivors Of Necmentioning
confidence: 99%
“…The model-derived dosing guidelines for morphine have not been implemented to date, as no consensus has been reached on its general applicability given the potentially different doses for different types of surgery (cardiac vs. non-cardiac surgery) or different subgroups (preterm vs. term neonates). A recent example in this respect is necrotising enterocolitis in preterm neonates, an extremely painful clinical situation, for which substantially higher morphine target concentrations were found necessary (63).…”
Section: Dosingmentioning
confidence: 99%
“…While for neonates and infants below 1 year, the dosing schedule hardly differs between these two models, the next step in pediatric morphine research is evaluating this morphine dosing regimen based on the BDE model for other indications than postoperative pain after major noncardiac surgery [1]. An observational study, for example, showed that higher dosages for NEC are required, most likely because this is a very painful condition [96]. These studies are important because so far the model-based dosing guidelines [1,95] are only corrected for differences in PK and not for type of pain or severity of illness.…”
Section: Model-based Dosingmentioning
confidence: 99%
“…In relation to postoperative pain, morphine requirements depend on duration and severity of surgery but also on the type of surgery, such as cardiac or abdominal surgery [3]. Newborns operated for NEC need much higher morphine dosages postoperatively than newborns operated on for other conditions [96].…”
Section: Pk-pd Relationshipmentioning
confidence: 99%